COMPARISON OF CENTRAL CORNEAL THICKNESS IN NORMAL TENSION GLAUCOMA AND PRIMARY OPEN ANGLE GLAUCOMA- A CROSS-SECTIONAL STUDY - Dubey Harshita, Dokania Ashutosh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Primary Open-Angle Glaucoma (POAG) and Normal TensionGlaucoma (NTG) are the two most prevalent subtypes of glaucoma, which is aleading cause of permanent blindness. The corneal thickness (CCT) significantlyaffects the measurement of IOP and development of glaucoma. The goal of this study is to compare the thickness of the Ganglion Cell Complex(GCC) and CCT in patients with NTG and POAG.